Highly improved ethanol gas-sensing performance of mesoporous nickel oxides nanowires with the stannum donor doping. (13th April 2018) - Wei, Junqi; Li, Xiaoqing; Han, Yanbing; Xu, Jingcai; Jin, Hongxiao; Jin, Dingfeng; Peng, Xiaoling; Hong, Bo; Li, Jing; Yang, Yanting; Ge, Hongliang; Wang, Xinqing
Abstract: Mesoporous nickel oxides (NiO) and stannum(Sn)-doped NiO nanowires (NWs) were synthesized by using SBA-15 templates with the nanocasting method. X-ray diffraction, transmission electron microscope, energy dispersive spectrometry, nitrogen adsorption/desorption isotherm and UV–vis spectrum were used to characterize the phase structure, components and microstructure of the as-prepared samples. The gas-sensing analysis indicated that the Sn-doping could greatly improve the ethanol sensitivity for mesoporous NiO NWs. With the increasing Sn content, the ethanol sensitivity increased from 2.16 for NiO NWs up to the maximum of 15.60 for Ni0.962 Sn0.038 O1.038, and then decreased to 12.24 for Ni0.946 Sn0.054 O1.054 to 100 ppm ethanol gas at 340 °C. The high surface area from the Sn-doping improved the adsorption of oxygen on the surface of NiO NWs, resulting in the smaller surface resistance in air. Furthermore, owing to the recombination of the holes in hole-accumulation lay with the electrons from the donor impurity level and the increasing the body defects for Sn-doping, the total resistance in ethanol gas enhanced greatly. It was concluded that the sensitivity of Sn-doped NiO NWs based sensor could be greatly improved by the higher surface area and high-valence donor substitution from Sn-doping.